A Novel Missense Mutation of the NSD1 Gene Associated with Overgrowth in Three Generations of an Italian Family: Case Report, Differential Diagnosis, and Review of Mutations of NSD1 Gene in Familial Sotos Syndrome - Gianluigi Laccetta; Francesca Moscuzza; Angela Michelucci; Andrea Guzzetta; Sara Lunardi; Francesca Lorenzoni; Paolo Ghirri (Frontiers Media S.A., 2017)
Sotos syndrome (SoS) is characterized by overgrowth of prenatal onset, learning disability, and characteristic facial appearance; it is usually due to haploinsufficiency of NSD1 gene at chromosome 5q35. An Italian child was born at 37 weeks of gestation (weight 2,910 g, 25th-50th centiles; length 50 cm, 75th centile; head circumference 36 cm, 97th centile) showing cryptorchidism on the right side, hypertelorism, dolichocephaly, broad and prominent forehead, and narrow jaw; the pregnancy was worsened by maternal preeclampsia and gestational diabetes, and his mother had a previous history of four early miscarriages. The patient showed neonatal jaundice, hypotonia, feeding difficulties, frequent vomiting, and gastroesophageal reflux. After the age of 6 months, his weight, length, and head circumference were above the 97th centile; psychomotor development was delayed. At the age of 9 years, the patient showed also joint laxity and scoliosis. DNA sequence analysis of NSD1 gene detected a novel heterozygous mutation (c.521T>A, p.Val174Asp) in exon 2. The same mutant allele was also found in the mother and in the maternal grandfather of the proband; both the mother and the maternal grandfather of the proband showed isolated overgrowth with height above the 97th centile in absence of other features of SoS. At present 23 familial cases of SoS have been described (two cases with mutation in exon 2 of NSD1 gene); no familial cases of SoS with mutation of NSD1 gene and isolated overgrowth have been reported. Probably, point mutations of NSD1 gene, and particularly mutations between exon 20 and exon 23, are not likely to affect reproductive fitness. Epigenetic mechanisms and intrauterine environment may influence phenotypes, therefore genetic tests are not useful to predict the phenotype but they are indispensable for the diagnosis of SoS. This is the first Italian familial case of SoS with genetic confirmation and the third report in which a missense mutation of NSD1 gene is found in three generations of the same family.